2006
DOI: 10.1161/01.res.0000247067.34173.1b
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Endocytosis of CD163 Mediates Hemoglobin-Heme Uptake and Determines the Noninflammatory and Protective Transcriptional Response of Macrophages to Hemoglobin

Abstract: Abstract-Heme toxicity contributes to the pathogenesis of chronic inflammatory diseases, atherosclerosis, and hemolysis associated vasculopathy. Macrophage clearance of cell free hemoglobin (Hb) is thus an essential homeostatic function of these cells. We examined the transcriptional response of human PBMC derived macrophages to Hb by gene array analysis. The observed noninflammatory macrophage response was characterized by induction of an antioxidative and antiinflammatory gene expression pattern with most pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
204
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(212 citation statements)
references
References 38 publications
(32 reference statements)
8
204
0
Order By: Relevance
“…Schaer and colleagues were the first to demonstrate that Hb-mediated induction of HO-1 through the CD163 receptor is a unique and defining transcriptional response in macrophages (148). In contrast to previous reports that used Hb contaminated with endotoxin (138,176), these macrophages are characterized by an anti-inflammatory gene expression profile and a unique three-gene signature of increased hmox-1 and glutamate-cysteine ligase modified (gclm) and suppressed [d]-aminolevulinate synthase (alas1), the rate-limiting enzyme in heme synthesis (142).…”
Section: Ho-1 Is a Heme-dependent Integrator Of The Mps Antiinflammatmentioning
confidence: 99%
See 1 more Smart Citation
“…Schaer and colleagues were the first to demonstrate that Hb-mediated induction of HO-1 through the CD163 receptor is a unique and defining transcriptional response in macrophages (148). In contrast to previous reports that used Hb contaminated with endotoxin (138,176), these macrophages are characterized by an anti-inflammatory gene expression profile and a unique three-gene signature of increased hmox-1 and glutamate-cysteine ligase modified (gclm) and suppressed [d]-aminolevulinate synthase (alas1), the rate-limiting enzyme in heme synthesis (142).…”
Section: Ho-1 Is a Heme-dependent Integrator Of The Mps Antiinflammatmentioning
confidence: 99%
“…This gene expression profile clearly distinguishes heme-induced CD163 + macrophages from the M1 or M2 macrophage subsets. Interestingly, the unique Hb-CD163 genetic signature is a direct result of increased intracellular heme, as treatment of macrophages with free heme (which enters the cell independent of the CD163 receptor) results in an identical transcriptional profile as compared to CD163-dependent ingestion of Hb (148). The CD163 + HO-1 + macrophage population is significantly expanded in the bone marrow and liver of patients with sepsis and in atherosclerotic plaques in heme-rich regions of neovascularization or intraplaque hemorrhage (IPH) (31,152).…”
Section: Ho-1 Is a Heme-dependent Integrator Of The Mps Antiinflammatmentioning
confidence: 99%
“…Low density lipoprotein receptor-related protein (CD91) is the receptor for hemopexin-heme complexes and is present in several cell types, including hepatocytes, M⌽, neurons, and syncytiotrophoblasts (98). After internalization, the haptoglobin-hemoglobin complexes are degraded in lysosomes (99). In contrast, the apohemopexin is recycled to the circulation after releasing heme into the cells (100).…”
Section: Recycling Of Heme and Heme Ironmentioning
confidence: 99%
“…Recent evidence has shown that CD163 is also upregulated acutely in neurons following ICH both in vivo and in vitro 12. By sequestering toxic hemolysis products, CD163 may play a key role in limiting inflammation and suppressing secondary injury following hemorrhagic injury 13, 14. CD163 expression by glia and infiltrating immune cells in perihematomal tissue was recently demonstrated in ICH patients, with expression peaking 72 h poststroke 15.…”
Section: Introductionmentioning
confidence: 99%